Reconstruction of Experiential Learning Methods in Islamic Religious Education Learning as a Strategy for Internalizing Religious Moderation Values - Saehu Abas; Riza Taufiqi Majid (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2025)
This study aims to: (1) identify the suitability of experiential learning methods in Islamic Religious Education on religious moderation; (2) explore the values of religious moderation that need to be internalized in PAI learning; and (3) analyze the challenges and opportunities of implementing experiential learning in strengthening the values of religious moderation in the PAI learning environment. This study uses a qualitative approach with library research methods, focusing on theoretical literature reviews. Data collection techniques were carried out through documentation with strict selection of literature sources, while data validity was obtained through source triangulation and member checking. Data analysis was conducted using a thematic approach and comparative analysis based on content analysis. The results of the study indicate that experiential learning in PAI learning is characterized by direct experience-based learning, observational reflection, abstract conceptualization, active experimentation, contextual learning, and the integration of multiple intelligences. The internalized values of religious moderation include: tolerance (tasamuh), justice (‘adl), balance (tawazun), moderation (wasathiyyah), dialogue (hiwar), wisdom (hikmah), and peace (salam). The challenges in its implementation include limitations in teacher competence, stakeholder resistance, infrastructure limitations, curriculum complexity, and differences in interpretation. Meanwhile, the opportunities are supported by government policies, increasing awareness of the importance of moderation, and the use of learning technology.